Complications in Operative Scheuermann Kyphosis: Do the Pitfalls Differ From Operative Adolescent Idiopathic Scoliosis?. Issue 5 (1st March 2015) - Lonner, Baron S.; Toombs, Courtney S.; Guss, Michael; Braaksma, Brian; Shah, Suken A.; Samdani, Amer; Shufflebarger, Harry; Sponseller, Paul; Newton, Peter O.
Abstract : Study Design: A prospective multicenter database of operative patients with Scheuermann kyphosis (SK) with minimum 1-year follow-up was studied for major complications compared with contemporaneous operative patients with adolescent idiopathic scoliosis (AIS) from the database. Objective: To evaluate complications associated with current surgical techniques in SK and AIS. Summary of Background Data: There is a paucity of literature regarding complications associated with SK surgical treatment, but prior data suggest an elevated neurological risk. Methods: Complication rates were compared using analysis of variance and Fisher exact test analyses. Major complications were those that were life-threatening, caused spinal cord, nerve root, or ocular injury or required reoperation including surgical site infections. A binary logistic regression determined the likelihood of complications based on diagnosis, levels fused, blood loss, operative time, and length of stay. Results: Ninety-seven patients with SK (57 males; mean age, 16.5 yr; 75.3° mean kyphosis) and 800 patients with AIS (622 females; mean age, 14.9 yr; 55.6° mean curvature) met inclusion criteria. Patients with SK had significantly more major complications than those with AIS (16.3% vs . 2.3%; P < 0.001). The SK group had more infections (10.3% vs . 0.75%) and reoperations (14.4% vs . 1.4%) ( P < 0.001). Operative time was longer and more levels were fused in the SK group ( P < 0.001). Surgical site infection was the most common complication. There were no significant differences in length of stay or blood loss. Patients with SK were 3.9× more likely to have a major complication than those with AIS (odds ratio: 0.26, P = 0.003). The number of levels fused was an independent predictor of major complications: each additional level fused increased the odds of a complication by 36% in both groups (odds ratio: 1.36, P = 0.034). Conclusion: Major complications are 3.9× more likely to occur in operative SK than in AIS. The number of levels fused is an independent risk factor for major complications. Patients with SK are at higher risk for infections and reoperation than those with AIS. Level of Evidence: 2 Abstract : Complications associated with Scheuermann kyphosis have not been well evaluated or compared with adolescent idiopathic scoliosis in a large cohort. Major complications are 3.9 times more likely to occur in operative Scheuermann kyphosis than in adolescent idiopathic scoliosis. Number of levels fused is an independent risk factor for major complications.